New Insights on the Regulation of Glucosinolate Biosynthesis via COP1 and DELLA Proteins in Arabidopsis Thaliana - Frerigmann, Henning; Hoecker, Ute; Gigolashvili, Tamara (Frontiers in Plant Science, 2021)
The biosynthesis of defensive secondary metabolites, such as glucosinolates (GSLs), is a costly process, which requires nutrients, ATP, and reduction equivalents, and, therefore, needs well-orchestrated machinery while coordinating defense and growth. We discovered that the key repressor of light signaling, the CONSTITUTIVE PHOTOMORPHOGENIC 1/SUPPRESSOR OF PHYTOCHROME A-105 (COP1/SPA) complex, is a crucial component of GSL biosynthesis regulation. Various mutants in this COP1/SPA complex exhibited a strongly reduced level of GSL and a low expression of jasmonate (JA)-dependent genes. Furthermore, cop1, which is known to accumulate DELLA proteins in the dark, shows reduced gibberellin (GA) and JA signaling, thereby phenocopying other DELLA-accumulating mutants. This phenotype can be complemented by a dominant gain-of-function allele of MYC3 and by crossing with a mutant having low DELLA protein levels. Hence, SPA1 interacts with DELLA proteins in a yeast two-hybrid screen, whereas high levels of DELLA inhibit MYC function and suppress JA signaling. DELLA accumulation leads to reduced synthesis of GSL and inhibited growth. Thus, the COP1/SPA-mediated degradation of DELLA not only affects growth but also regulates the biosynthesis of GSLs.